Psychological experience of breastfeeding among primiparous women with lactating mastitis: A qualitative research - Ye LI; Jingjin XU; Ling TANG (Wolters Kluwer Medknow Publications, 2024)
Objective: The objective of this study is to comprehensively understand the psychological experience of primiparous women during breastfeeding while dealing with lactating mastitis and to establish a reliable foundation for tailored support measures. Methods: Twenty primiparous mothers from a tertiary hospital in Beijing between January and March 2023 were chosen using purposive sampling for semi-structured interviews. After conducting 20 interviews, data saturation was achieved. The Colaizzi's seven-step analytical approach was employed to analyze, summarize, and refine the identified themes. Results: Among primiparous women afflicted by lactating mastitis, the primary themes regarding breastfeeding attitudes included three key aspects: (1) uncertainty during the initial diagnosis phase, (2) intricate emotional journey during treatment, and (3) positive psychological outlook during the recovery stage. Conclusion: Primiparous women undergoing lactating mastitis experience substantial physical and psychological strain. It is crucial for medical personnel, family caregivers, and society at large to be attuned to the emotions of these patients. Tailored support measures should be offered to enhance patients' physical and mental well-being and facilitate disease recovery.